Planning of construction supply system in constrained conditions using the dynamic programming method - Ya. D. Ageeva; Yu. A. Chirkunov; A. A. Lapidus (Vestnik MGSU)
Introduction. The application of the dynamic programming method is widely used to solve optimization problems in construction. Depending on the complexity of the project and the conditions during the construction of buildings and structures, making optimal decisions may require the analysis of a large amount of data and options. Dynamic programming allows you to consider an optimization problem as a sequence of subproblems that can be solved separately and then combined into an overall solution. This makes it possible to simplify the process of planning and project management, which is relevant for making organizational and technological decisions in the material and technical supply of construction in dense urban areas, as well as for increasing the efficiency and competitiveness of the construction industry as a whole.Materials and methods. The study uses the method of mathematical formalization of conditions, efficient supply of resources, the method of dynamic programming and the method of graph interpretation of results.Results. The supply system for construction production was optimized for multi-threaded organization of work; based on the optimization results, the optimal distribution of resources was determined and a network diagram of the movement of cargo flows was constructed during the considered stage of building construction. An algorithm was developed for planning the supply schedule for the continuous method of delivering resources to the construction site.Conclusions. The organization of resource support for construction and installation work in cramped conditions must take into account a number of restrictions caused by these conditions. Reducing inventory is critical to maintaining a stock-free supply chain. In addition, with the continuous construction method, there is a risk of increasing inventory due to the dynamics of demand for materials and equipment while work is carried out in parallel. The use of the dynamic programming method made it possible at the planning stage to avoid the occurrence of shortages and exceeding the maximum stock of material resources and to select their optimal distribution at the considered stage of construction and installation work.